Contribution to the knowledge of Autolyca herculeana (Phasmatodea: Pseudophasmatidae): record from Honduras and first descriptions of the female and eggs - Oviedo-Maas, Allyson; Flores-Suazo, Suany M.; Hernandez-Osorio, Juan C.; Mérida, Julio E.; Cruz, Gustavo A. (Zootaxa, 2026)
The presence of Autolyca herculeana Conle & Hennemann, 2002 is here documented from Honduras with precise locality data. Although Honduras had previously been included in global checklists of the genus, no published material with specific localities was available. This study also provides the first morphological descriptions of the female and eggs of the species, as well as notes on the species’ natural history, contributing to the current knowledge of the genus in Central America.